(untitled) (Journal of Oriental Studies, 2016)
At-Ta’riib (also at-Taarib) along with «al-Ishtiqaq», «an-Nacht» is one of the ways of formation of lexical units in Arabic. The Arabic term «at-Ta’riib» corresponds to the term «borrowings» as a way of term formation. However, the use of Masdar «at-Ta’riib» formed from the verb ‘Arraba arabization. This method is widely used as a common language in the lexicon (alal-lugat’Amma), and in a special language vocabulary (al-Lugat al-Hassa), consisting of several sublanguages. This paper attempts to consider a way of «at-Ta’riib» in the IT terminology within the dominance of the English (American) language.